Biguanide- and Oligo(Ethylene Glycol)-Functionalized Poly(3,4-Ethylenedioxythiophene): Electroactive, Antimicrobial, and Antifouling Surface Coatings - Ayalew, Hailemichael; Ali, Syed Atif; She, Jia-Wei; Yu, Hsiao-hua (Frontiers in Chemistry, 2022)
The challenge of infectious diseases remains a critical concern to the global public health. Recently, it is common to encounter touch-screen electronic devices everywhere to access services. The surface of such devices may easily get contaminated by an infected person, which leads to transmission of infectious diseases between individuals. Moreover, the challenge is complicated by surgical infections from implantable biomedical devices. Such problems can be minimized by the use of long-term active antimicrobial surface coatings. We present herein the preparation of novel electroactive antimicrobial surface coatings through the covalent attachment of the biguanide moiety onto 3,4-ethylenedioxythiophene (EDOT). The biguanide-functionalized EDOT (EDOT-BG) was thus electropolymerized on different substrates to give the corresponding poly(EDOT-BG) polymer. The poly(EDOT-BG) polymer showed an excellent bactericidal efficiency (∼92% bacterial death) and excellent biocompatibility with mammalian cells. Furthermore, the antimicrobial EDOT-BG was electro-copolymerized with antifouling tetra ethylene glycol functionalized-EDOT (EDOT-EG4) to give a multifunctional poly(EDOT-EG4-co-EDOT-BG) copolymer. The poly(EDOT-EG4-co-EDOT-BG) copolymer showed excellent resistance to protein adsorption and mammalian/bacterial cell binding without losing its bactericidal efficiency. These novel materials can be applied to domestic and bioelectronic devices to minimize infectious diseases.